Possible role of alpha-lipoic acid in the treatment of peripheral nerve injuries - Ranieri, Maurizio; Sciuscio, Manuela; Cortese, Annamaria; Stasi, Marilena; Panza, Francesco; Megna, Marisa; Fiore, Pietro; Santamato, Andrea (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Recent findings on the antioxidant effects of pretreatment with α-lipoic acid (α-LA) on the crush injury of rat sciatic nerve confirm the possible usefulness of α-LA administration in humans with peripheral nerve injuries. We discussed this issue in relation with our recent results in which the combined employment of α-LA and γ-linolenic acid with a rehabilitation program for six weeks reduced sensory symptoms and neuropathic pain in patients with compressive radiculopathy syndrome from disc-nerve root conflict in comparison with patients submitted to rehabilitation program alone for six weeks.